PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN FINANCIAL LEVERAGE TERHADAP PERATAAN LABA: (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2023) - Susanti Diana Mahri; Ahmad Zuliansyah; Suhendar Suhendar (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to examine the influence of firm size, profitability, and financial leverage on income smoothing in manufacturing companies within the food and beverage subsector listed on the Indonesia Stock Exchange during the 2020–2023 period. Income smoothing is an important issue because it may affect the quality of accounting information used by investors, creditors, and other stakeholders in making economic decisions.Methods: The research employs a quantitative approach using secondary data obtained from annual financial statements. The sample was selected through a purposive sampling technique, resulting in 31 companies with a total of 124 observations. Data analysis was conducted using multiple linear regression, preceded by classical assumption testing to ensure the validity of the model. Results: The results show that firm size and financial leverage have a positive and significant effect on income smoothing, while profitability has a negative and significant effect. Simultaneously, the three independent variables were proven to influence income smoothing practices, with the model explaining 81.3% of the variation in income smoothing.Conclusion and suggestion: These findings indicate that internal company factors play an important role in driving managerial incentives to perform income smoothing. The study recommends strengthening financial reporting transparency and oversight to reduce such practices. Future research is suggested to incorporate additional variables such as ownership structure, audit quality, and corporate governance mechanisms and to broaden the research scope to provide a more comprehensive understanding of the determinants of income smoothing. Keywords: Financial Leverage, Firm Size, Income Smoothing, Profitability